Fertigation for High Productivity and Resource Conservation - Soman, P. (International Journal of Economic Plants, 2015)
Technologies for cultivation of crops have been changing over the years. Adherence to the principles of conservation, high use efficiency and higher productivity with optimum inputs and the very idea of crop production as a business venture; all these are leading to the increased adoption of high technological (high-tech) input delivery mechanisms in Agriculture. Among the different inputs to crop production management of water and fertilizer assume highest priority by virtue of the fact that the country has shortage for both and both are essential for any type of crops. Adoption of drip irrigation results in high productivity besides water conservation. If application of fertilizers is also done through the drip system; then the increases in yield and quality of the produce can be multifold as evidenced for several crops over the years. Fertigation is the technique of supplying dissolved fertilizer to crops through an irrigation system. When combined with an efficient irrigation system both nutrients and water can be controlled and managed to obtain the maximum possible yield of marketable product from a given quantity of these inputs. Therefore it is more or less accepted that generaliszed fertilizer recommendations can be utilized for fertilization plan for a specific crop and its different cultivars. Nonetheless, fertigation gives a tool to make regional modifications of the fertilizer quanta and timing based on soil and leaf or petiole analysis. A far rapid method of adjustments in the application rate to achieve precision is possible.